Voices from the Hotel Industry: Employee Opinions on Motivation, Job Satisfaction, Performance and Job Stress - Pantha, Sujata; Yadav, Lekhnath; Adhikari, Subash; Hamal, Krishna (International Journal of Atharva, 2024)
The study assessed employee opinions of motivation, work satisfaction, performance, and job stress in the hotel business.  Demographic data found a diverse workforce by gender, age, and education level, with the majority aged 18 to 27. Result display Challenging and meaningful work emerged as the most important motivation for employees, followed by financial remuneration and supportive managers. Organizations generally compensate their staff through open acknowledgement. The majority of respondents indicated job satisfaction, with money being the most relevant element, followed by social interactions and working circumstances. External elements that added value to the employment included physical work, promotion opportunities, relationships with superiors and coworkers, inventiveness, and organizational structure and culture. Internal factors influencing performance identified education level as the most important. The participants assessed their overall job performance as outstanding. Despite high job satisfaction, a significant share experienced workplace stress, largely from workload. Taking breaks was one of the coping mechanisms used, emphasizing the need of stress management in the hospitality business. The study provides insights for hotel management on how to improve employee well-being and organizational performance in a rapidly changing business.